Innovation in Complaints about Targeted Electricity Subsidy Participation in the Context of Improving Public Services - Elisabet Yakoba; Achmad Lutfi (Borong Newinera Publisher, 2023)
In order to improve the quality of public services, one of the efforts made by the government is to make a new breakthrough through the targeted electricity subsidy complaint application (PEDULI). This research aims to analyze innovations in improving public services using the mobile-based PEDULI application. This research uses 5 (five) innovation indicators according to Rogers, namely relative advantage, compatibility, complexity, triability, and observability which are used to analyze improvements in public services, in this case the targeted electricity subsidy complaint service through the mobile-based PEDULI application. This research uses post-positivism methods which are carried out using data collection techniques using in-depth interviews, observation and documentation studies. Based on the research, the results show that in mobile-based public service innovation complaints about targeted electricity subsidies (PEDULI) have experienced a good increase and have met the public's need to make complaints regarding targeted electricity subsidy membership.